Metabolomics and transcriptomics profiling of three Paris species with varied polyphyllin compositions - Ping Xu; Jia Chen; Qi Mi; Wenchun Li; You Lu; Wenxiu Luo; Mengwen Yu; Xuan Zhang; Zhenhua Tu; Honggao Xu; Guowei Zheng (Scientific Data)
Abstract Most of the species in Paris have important medicinal values in China. Polyphyllins are the key components in Paris, with varying levels and compositions among different species. This study investigated polyphyllin compositions of 206 Paris samples from 16 different producing areas. 9 Paris polyphylla var. yunnanensis, 3 Paris fargesii, and 3 Paris forrestii were selected based on polyphyllin levels and composition for metabolome and transcriptome analysis. A total of 1,243 metabolites were identified among these samples, along with 92.11 Gb of full-length transcriptome data. This study provides potential candidate genes involved in polyphyllins synthesis in Paris, aiming to facilitate the biosynthesis of different polyphyllins.